Pengembangan Pengembangan Media Gform Chatroom Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SDN Tlogo 02 Kabupaten Blitar - Irvan Safi'i, Mochammad Dwi; Alfi, Cindya; Fatih, Mohamad (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2024)
An essential part of the learning process is assessment. Assessments are performed to look for information or fundamental factors pertaining to the accomplishment of learning objectives. The lack of interesting assessments causes students to get bored with the questions given, besides that teachers tend to be reluctant to innovate. Therefore, teachers are at least able to prepare test and non-test instruments. In addition, pupils' lack of interest in learning causes issues with the learning process. Due to modifications in how pupils study as a result of the pandemic that has ended, children' levels of learning motivation have declined. This is characterized by reduced discipline when attending lessons. This research aims to develop a chatroom gform assessment (Google Form with conversation features). The existence of a gform chatroom learning assessment can attract students' attention thereby improving students' critical thinking skills. The learning assessment that was developed can help students develop their capacity for critical thought. Utilizing the R&D/Research and Development research methodology, the media design model or technique used in this study is the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. Tests and questionnaires were utilized as the data collection methods in this study. A total of 21 pupils from class V participated in the study. evaluated by media experts, with a feasibility percentage of 81.4. Material expert evaluation with an 86.4 percent feasibility rate. Students' critical thinking abilities improve in the "high" category, according to the comparison of their scores before and after using the gform chatroom media.